Putative type specimens of Satyrichthys (Scorpaeniformes: Peristediidae) in the Bleeker collection of the Naturalis Biodiversity Center, Leiden, The Netherlands - van Oijen, Martien J.p.; Kawai, Toshio; Loots, Ineke (Zootaxa, 2013)
The presumed type status of the two remaining specimens of Peristedion moluccense Bleeker 1850 in the collection the Naturalis Biodiversity Center was examined by comparing them to descriptions in two Bleeker papers and an unpublished manuscript by Bleeker written for the Atlas Ichthyologique. Latin, French and Dutch parts of these papers were translated into English. The Dutch description of P. laticeps Schlegel 1852 was also translated. In the course of this study it became clear why Bleeker considered P. laticeps, a as a synonym of P. moluccense.